2012
DOI: 10.1016/j.apal.2012.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The relational model is injective for multiplicative exponential linear logic (without weakenings)

Abstract: We prove a completeness result for Multiplicative Exponential Linear Logic (MELL): we show that the relational model is injective for MELL proof-nets, i.e. the equality between MELL proof-nets in the relational model is exactly axiomatized by cut-elimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…For instance, while it is well-known that the coherent model of second order linear logic [13] is not dinatural ( [11]), it can be easily seen that it satisfies the Yoneda isomorphism. Hence it can be conjectured that the model is injective (in the sense of [7]) with respect to ∃-linkings for MLL2 Y .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, while it is well-known that the coherent model of second order linear logic [13] is not dinatural ( [11]), it can be easily seen that it satisfies the Yoneda isomorphism. Hence it can be conjectured that the model is injective (in the sense of [7]) with respect to ∃-linkings for MLL2 Y .…”
Section: Discussionmentioning
confidence: 99%
“…We give here a functorial definition of ends and coends which can be easily deduced from the usual definition (see[28]). 7 We will abbreviate δ x 1 ,...,x n ,a and ω x 1 ,...,x n ,a simply as δ a and ω a , respectively.…”
mentioning
confidence: 99%
“…box : |R| → A is a morphism of oriented graphs, 6 the box-function of R, such that box F induces a partial bijection from…”
Section: Dill Proof-structuresmentioning
confidence: 99%
“…A MELL proof-structure is an oriented graph together with some additional information to identify the content and the border of each box. This additional information can be provided either informally, just drawing the border of each box in the graph [14,10,19], but then the definition of MELL proof-structure is not rigorous; or in a more formal way [6,15,7], but then the definition is highly technical and ad hoc; 2. A MELL proof-structure is an inductive oriented graph [17,22,26,8], i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This investigation has been extended to concurrent strategies by Mimram and Melliès [25,26]. De Carvalho showed that the relational model is injective for MELL [11]. In another direction, [4] provides a fully complete model for MALL without game semantics, by using a glueing construction on the model of hypercoherences.…”
Section: Extensions and Related Workmentioning
confidence: 99%